Annual Variation in Flowering Phenology, Pollination, Mating System, and Pollen Yield in Two Natural Populations of Schima wallichii (DC.) Korth - Vinod Prasad Khanduri; C. M. Sharma; K. S. Kumar; S. K. Ghildiyal (The Scientific World Journal)
Background. Schima wallichii is a highly valuable tree of tropical forest in north-east Himalaya region that grows naturally in a wide range of altitudes between 750 and 2400 m asl with varying environments. Flowering phenology of tropical tree species at population level is generally ignored and therefore a detailed knowledge of flowering and fruiting patterns of important multipurpose tree species is critical to the successful management of forest genetic resources. Materials and Methods. The study was conducted at two different altitudes (i.e., 750 m and 900 m asl) in the tropical semideciduous forest of north-east Himalaya. The floral phenology including flowering synchrony in the populations, anthesis, anther dehiscence, stigma receptivity, pollinators visitation frequency, and mating system including index of self-incompatibility were worked out in Schima wallichii according to the ear-marked standard methods given by various scientists for each parameter. Results. The flowering period in Schima wallichii varied from 33 to 42 days with mean synchrony of 0.54 to 0.68 between the populations. The stigma was receptive up to 2.5 days only and showed slightly protandrous type of dichogamy. Average pollen production ranged between 6.90 × 107 pollen per tree in 2007 and 15.49 × 108 pollen per tree in 2011. A three-year masting cycle was noticed in this species. The frequency of visitation of honey bees was fairly high (5.2 ± 1.12 visits/flower/hour) as compared to other pollinators. The hand pollination revealed maximum fruit (74.2 ± 5.72%) and seed (70.8 ± 7.46%) settings. Conclusions. The variation in flowering phenology and pollen yield individually and annually along with temporal separation in anther dehiscence and pollinator’s visitation cause pollen limited reproduction, which ultimately influences the reproductive success in Schima wallichii.